Ruminant prion disease detection and characterisation using protein misfolding cyclic amplification - O'Connor, Matthew (2017)
Prion diseases or transmissible spongiform encephalopathies (TSE) are characterised by the accumulation of a misfolded conformer (PrPSc) of a host encoded protein (PrPC). The misfolding event that leads to the formation PrPSc can be replicated in the in vitro amplification technique, protein misfolding cyclic amplification (PMCA). This thesis focuses on the application PMCA to study multiple aspects of prion misfolding in relation to ruminant prion diseases, specifically developing techniques to detect and characterise PrPSc in scrapie and BSE infections. Utilising recombinant hamster PrP (rPrP) as substrate in PMCA, multiple genotypes of scrapie were successfully amplified in an attempt to describe a quantifiable technique applicable to a wide range of scrapie isolates. Observations of non-specific protease resistant rPrP formation was investigated with modifications to the PMCA methodology, which ultimately proved unsuccessful in reducing non-specific protease resistant rPrP. Using brain PrPC as substrate, the quantitative PMCA technique was piloted with BSE to correlate in vitro replication efficiency with infectious titre in mouse bioassay, but no correlation was identified. Atypical forms of BSE occur primarily in older cattle, are asymptomatic and thought to be spontaneous diseases. None the less, infection models in rodents and primates have identified the zoonotic potential of H-type and L-type BSE. Therefore PMCA methods were developed which were able to successfully amplify both atypical forms of BSE. In particular, sensitive detection and discrimination from classical BSE was demonstrated for H-type BSE, which has not previously been amplified in PMCA. H-type BSE could be detected in 1x10¬-12 g brain material and was discriminated from classical BSE by increased protease sensitivity, relatively high molecular weight and antibody reactivity. Evidence exists for co-infection of TSE strains, yet scrapie and BSE co-infection in an ovine host remains unaddressed. To study the disease progression and tissue dissemination of co-infections a PMCA assay capable of specifically amplifying BSE PrPSc in the presence of excess scrapie was applied to artificially mixed brain homogenates containing BSE and scrapie, and compared to current statutory strain typing methods. The PMCA was found to have sensitivity and specificity of 100% in mixes containing 0.1% BSE and 99.9% scrapie brain material, which was more effective than conventional strain typing methods. The assay was then applied to the brain, spleen and lymph of scrapie and BSE experimental co-infections in two genotypes of sheep, and to animals which belonged to a flock with endemic natural scrapie and that also received experimental BSE infections. The PMCA data demonstrated that sheep with PRNP genotype ARQ/ARQ (at amino acid positions 134, 154 and 171) were resistant to BSE in a co-infection scenario. In sheep with PRNP genotype of VRQ/ARQ, mixed infections could occur, and animals with scrapie PrPSc only in the brain could harbour BSE PrPSc in peripheral tissues. Co-infection was also possible in sheep with natural scrapie infections. The assay was compared to conventional testing methods of western blotting, PrPd profiling and immunohistochemistry and displayed superior sensitivity in BSE detection. PMCA amplification of bovine BSE isolates in ovine substrates identified several instances in which the molecular characteristics of the PrPSc was scrapie-like in terms of molecular weight, antibody reactivity and glycoform profile, and in some cases PrPSc characteristic of BSE could no longer be recovered. This occurred in a genotype specific manner, ‘molecular switching’ was only apparent in ovine substrate VRQ/VRQ in accordance with previous findings. These results raise the possibility of such an event occurring in in vivo ovine BSE infections and the zoonotic potential of these scrapie like conformers are yet to be fully addressed.